2022
DOI: 10.1128/mbio.03688-21
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Weakens the NAFLD/NASH Process by Facilitating Intestinal Barrier Restoration Depending on the Gut Microbiota

Abstract: The morbidity of NASH has increased, with limited effective treatment options. IL-17 plays a protective role in the gut mucosa in high-fat-diet (HFD)-related metabolic disorders, and HFD-related microbiota dysbiosis is responsible for a decreased number of T helper 17 (T H 17) cells in the lamina propria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The deletion of Akt1 and Akt2 in the liver has been shown to cause liver inflammation and hepatocyte death, and the use of PI3K/AKT inhibitors has been shown to significantly enhance the degree of liver damage in mice ( Reyes-Gordillo et al, 2019 ). Furthermore, the IL-17 and VEGF signaling pathways may contribute to a decrease in HF ( Kumar et al, 2016 ; Fabre et al, 2018 ; Martínez-López et al, 2019 ; Qiao et al, 2020 ; Ghanim et al, 2021 ; He et al, 2022 ). Huiji Pan et al discovered that gut microbiota influence H-L + HFD-induced liver fibrosis through alteration of the hepatic IRS1/Akt/mTOR signaling pathway ( Pan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of Akt1 and Akt2 in the liver has been shown to cause liver inflammation and hepatocyte death, and the use of PI3K/AKT inhibitors has been shown to significantly enhance the degree of liver damage in mice ( Reyes-Gordillo et al, 2019 ). Furthermore, the IL-17 and VEGF signaling pathways may contribute to a decrease in HF ( Kumar et al, 2016 ; Fabre et al, 2018 ; Martínez-López et al, 2019 ; Qiao et al, 2020 ; Ghanim et al, 2021 ; He et al, 2022 ). Huiji Pan et al discovered that gut microbiota influence H-L + HFD-induced liver fibrosis through alteration of the hepatic IRS1/Akt/mTOR signaling pathway ( Pan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Estrogen signaling pathway: The lack of estrogen accelerates hepatic steatosis progression, in particular, which is exposed noticeably to post-menopausal women with metabolic disorders 28 . (3) Interleukin-17 (IL-17) signaling pathway: A report demonstrated that IL-17 could enhance intestinal epithelial layer and diminish dysbacteriosis-caused intestinal damage and other organs injury incited by a diet 29 . Noticeably, Relaxin signaling pathway, Estrogen signaling pathway, and IL-17 signaling pathway are related directly to JUN in the treatment of NAFLD, indicating that the three signaling pathways might exert its therapeutic value on NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…114 Furthermore, a recent study comparing IL-17 À/À mice fed an MCD diet and IL17 +/+ mice fed an MCD diet found that IL-17 is crucial for regulating the balance of gut microbiota and intestinal barrier integrity. 115 In addition, the study suggested that the protective effect of IL-17 in maintaining intestinal barrier integrity may outweigh its potential for tissue damage in NAFLD/NASH. However, further research is needed to fully understand the specific mechanisms involved.…”
Section: Changes In Microbesmentioning
confidence: 99%